2013
DOI: 10.1007/s10725-013-9855-y
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to naphthoquinones: juglone as a case study

Abstract: The effects of juglone (JG) on the endogenous growth, growth in the presence of either indoleacetic acid (IAA) or fusicoccin (FC) and on proton extrusion were studied in maize coleoptile segments. In addition, membrane potential changes were also determined at chosen JG concentrations. It was found that JG, when added to the incubation medium, inhibited endogenous growth as well as growth in the presence of either IAA or FC. Simultaneous measurements of growth and external pH indicated that inhibition of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 53 publications
3
28
0
Order By: Relevance
“…Analyses of the influence of juglone have also been the focus of studies on physiological parameters such as photosynthesis or mitochondria functioning and have indicated that juglone disturbs these physiological processes [3,4,22,27]. In the light of the above-mentioned studies, the results presented here, which show a positive influence of juglone on tomato plants, are rather unique.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Analyses of the influence of juglone have also been the focus of studies on physiological parameters such as photosynthesis or mitochondria functioning and have indicated that juglone disturbs these physiological processes [3,4,22,27]. In the light of the above-mentioned studies, the results presented here, which show a positive influence of juglone on tomato plants, are rather unique.…”
Section: Discussionmentioning
confidence: 53%
“…In growth analyses, the treatment usually lasted several weeks and the effect was harmful [19,21,28]. In experiments in which the physiological response or gene expression was investigated, the treatment with juglone lasted only hours [3,4,29,30]. Therefore, it is difficult to compare our results with most of the literature data.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, we showed that juglone (5-hydroxy-1,4-naphthoquinone), which is a naturally occurring naphthoquinone in walnut trees (Juglans), inhibited both IAA-induced growth and proton extrusion in maize coleoptile cells in a concentration-dependent manner. The strong correlation between both of these magnitudes suggested that the mechanism by which juglone inhibits IAA-induced growth involves the inhibition of PM H + -ATPase activity (Rudnicka et al 2014). Quite recently, Kurtyka et al (2016) published a paper in which the authors obtained that juglone and lawsone contribute to H 2 O 2 generation and activity of ROS scavenging enzymes (SOD, POX and CAT) in maize coleoptile segments.…”
Section: Discussionmentioning
confidence: 99%